Tinjauan Yuridis Terhadap Ancaman dan Upaya Penanggulangan Tindak Pidana Perundungan di Dunia Maya (Cyberbullying) - Kayla Astrida Aristianto (Pusat Riset dan Inovasi Nasional, 2024)
Current technological advances have positive and negative effects. While there are many benefits to be gained from this advancement, it also has many negative effects for users. The number of crimes that occur in cyberspace, such as cyberbullying, is one of the negative impacts that must be addressed and must be followed up when imposing sanctions on perpetrators. Because it has had a negative impact on victims of cyberbullying, the perpetrator must be given a deterrent punishment. Normative juridical research methods were used in this research, and the data collection method used was literature study. The government has established laws regarding the criminal act of cyberbullying, as stated in the Criminal Code and the ITE Law. The aim of this law is to eradicate and minimize cyberbullying perpetrators and acts.